Assessing the existence of the J-curve effect on trade in Malaysian forest products - Abdul Samad, Abdul Rahim; Othman, Mohd Shahwahid (Faculty of Economics & Administration, University of Malaya and Malaysian Economic Association, 2014)
This paper examines the dynamic effect of Malaysian exchange rate indices on bilateral trade for Malaysian forest products namely fibreboard, particle board and pulp for paper. Special attention is given to investigate the J-curve hypothesis: whether or not the trade balance for Malaysian forest products trade benefits from a decline in the value of the Ringgit Malaysia (RM). We adopt the autoregressive distributed lag (ARDL) approach to cointegration in estimating the annually bilateral trade data of Malaysian forest products trade with various countries in the world from 1970 to 2010. We find no evidence of the J-curve phenomenon for the Malaysian forest products trade. In the long run analysis, we found that Malaysian exchange rate is insignificant in influencing the Malaysian forest products trade balance. This implies that there are no changes in the trade balance for fibreboard, particle board and pulp for paper trade, regardless of whether the Malaysian exchange rate depreciates or appreciates. However, income variables are found to be important factors in determining the Malaysian trade only in pulp for paper product.